Victimized in Amsterdam: the organized reaction - Hauber, Albert R. (Crime, law and social change, 1999)
This article deals with the effects of a unique victim assistance project for victimized tourists, the Amsterdam Tourist Assistance Service (ATAS). ATAS intervention turns out to have a direct impact on victims to the extend that the negative consequences or the victims are reduced. Besides, ATAS intervention has a function on repairing Amsterdam's image that probably was damaged aftre the victimization.